Learning style preferences among form 4 Male and female arts students in two urban Schools - Mustafa, Rosnah; Pung, Wun Chiew; Rinong , Faridah (Malaysian English Language Teaching Association (MELTA), 2009)
This study aimed to identify the perceptual learning style preferences (PLSP) of Form 4 Arts male and female students in learning literature in English. It also attempted to investigate whether teachers were aware of, and subsequently varied their instructional strategies to cater to students’ PLSP. Data were collected through questionnaires and semi-structured interviews. The results revealed although both male and female students displayed similar PLSP patterns, female students showed greater preference for certain learning styles. The results also showed teachers’ instructional strategies were seldom varied despite them being aware of their students’ PLSP. Implications of the fi ndings for practical applications of PLSP research in language classrooms are discussed.